Applying a Women’s Health Lens to the Study of the Aging Brain - Taylor, Caitlin M.; Pritschet, Laura; Yu, Shuying; Jacobs, Emily G. (Frontiers in Human Neuroscience, 2019)
A major challenge in neuroscience is to understand what happens to a brain as it ages. Such insights could make it possible to distinguish between individuals who will undergo typical aging and those at risk for neurodegenerative disease. Over the last quarter century, thousands of human brain imaging studies have probed the neural basis of age-related cognitive decline. “Aging” studies generally enroll adults over the age of 65, a historical precedent rooted in the average retirement age of U.S. wage-earners. A consequence of this research tradition is that it overlooks one of the most significant neuroendocrine changes in a woman’s life: the transition to menopause. The menopausal transition is marked by an overall decline in ovarian sex steroid production – up to 90% in the case of estradiol – a dramatic endocrine change that impacts multiple biological systems, including the brain. Despite sex differences in the risk for dementia, the influence that biological sex and sex hormones have on the aging brain is historically understudied, leaving a critical gap in our understanding of the aging process. In this Perspective, we highlight the influence that endocrine factors have on the aging brain. We devote particular attention to the neural and cognitive changes that unfold in the middle decade of life, as a function of reproductive aging. Next, we consider emerging evidence from animal and human studies that other endocrine factors occurring earlier in life (e.g. pregnancy, hormonal birth control use) also shape the aging process. Applying a women’s health lens to